The Use Think-Pair-Share Strategy By Teacher For Students’ Speaking Skills - Amira, Naura Mutiaraina (Jurnal Ilmu Multidisiplin Indonesia, 2024)
This study aims to explore the use of the Think-Pair-Share strategy by teacher to enhance students’ speaking skills at SMP Negeri 1 Karawang Barat. A descriptive qualitative method was employed to collect data through classroom observations and interviews with teachers and students. Participants included VIII C students at SMP Negeri 1 Karawang Barat who engaged in Think-Pair-Share sessions during the research period. The findings indicate that implementing the Think-Pair-Share strategy significantly improves students’ speaking skills through small group discussion activities. Students demonstrated improvements in verbal abilities, the ability to articulate ideas, and enhanced confidence in public speaking. Data analysis also revealed that social interaction among students when using this strategy helped deepen their understanding of learning materials and fostered collaboration among classmates. This study highlights the importance of active learning strategies in enhancing students’ speaking skills in secondary schools. The implications of this research suggest that integrating the Think-Pair-Share strategy can positively contribute to the development of language learning curricula in schools by promoting active student participation, improving their speaking skills, and facilitating collaborative learning.